Exercise and pharmacologic stress-induced interlead T-wave heterogeneity analysis to detect clinically significant coronary artery stenosis. (1st January 2020) - Silva, Anderson C.; de Antonio, Victor Z.; Sroubek, Jakub; Gervino, Ernest; Ho, Kalon; Medeiros, Sofia A.; Silva, Fernanda Tessarolo; Pedreira, Giovanna C.; Stocco, Fernando G.; Nearing, Bruce D.; Verrier, Richard L.
Abstract: Background: Despite widespread use of ETT and vasodilator-stress with myocardial perfusion imaging (MPI) for noninvasive detection of flow-limiting coronary artery disease, there is continued need to improve diagnostic accuracy. We examined whether measurement of interlead T-wave heterogeneity (TWH) during exercise tolerance testing (ETT) or pharmacologic stress testing improves detection of stenoses in large epicardial coronary arteries. Methods: All 137 patients at our institution who underwent diagnostic coronary angiography within 0 to 5 days after ETT ( N = 81) or dipyridamole IV infusion ( N = 58) in 2016 were studied, including 2 patients with both tests. Cases ( N = 93) had angiographically significant stenosis (≥50% of left main or ≥ 70% of an epicardial coronary artery ≥2 mm in diameter); controls ( N = 44) did not. TWH, i.e., interlead splay of T waves, was determined by second central moment analysis from precordial leads by an investigator blinded to angiographic results. Results: At rest, TWH levels were similar for cases and controls. ETT and dipyridamole stress testing increased TWH by 69% ( p < 0.0001) and 27% (p < 0.0001), respectively, in cases. In controls, TWH did not change. Areas under the ROC curves for TWH increase for any flow-limiting coronary artery stenosis were 0.737 ( p < 0.0001) for ETT and 0.818 (p < 0.0001) for dipyridamole stress testing. By contrast, neither ST-segment changes during ETT ( p = 0.12) nor MPI during dipyridamole stress testing ( p = 0.60) discriminated cases from controls. Conclusions: TWH measurement is a novel method that improves detection of angiographically confirmed flow-limiting stenoses in large epicardial coronary arteries during both ETT and MPI during pharmacologic stress testing with dipyridamole. Highlights: T-wave heterogeneity (TWH) is a novel measure of interlead splay of ECG waveforms. TWH detects flow-limiting stenoses during ETT (AUC, 0.737, p < 0.0001) and MPI (AUC, 0.818, p < 0.0001). ST-segment changes during ETT (p = 0.12) and MPI (p = 0.60) did not detect CAD. Combining TWH with MPI improves specificity (to 95%), odds ratio (to 36.54), and positive likelihood ratio (to 13.16). TWH testing is performed using standard protocols, equipment, and electrodes.